Efficacy of Exclusive Enteral Nutrition in Pediatric Crohn’s Disease - Rodrigues, Luís; Moeda, Sofia; Loreto, Helena; Azevedo, Sara; Asseiceira, Inês; Maltez, Catarina; Fernandes, Ana; Mourato, Ana Paula; Lopes, Ana Isabel (Nutrición Clínica y Dietética Hospitalaria, 2021)
Introduction: Exclusive enteral nutrition (EEN) is recommended as first line therapy for mild to moderate Crohn’s disease (CD) to induce remission in pediatric patients. It involves the use of a whole protein formula given exclusively for six to eight weeks. Aims: To report the preliminary experience of a tertiary care center in Portugal, concerning the efficacy and tolerance of EEN in pediatric patients with CD. Materials and methods: Retrospective descriptive study of pediatric CD patients who received EEN as induction of remission therapy between January/2014 and June/2019. Clinical and laboratory parameters were assessed, including clinical disease activity and nutritional status before and immediately after treatment. Results: In the study period, 37 patients were diagnosed with CD; 19 were included in the study, 17/19 (89.5%) completed the EEN therapy and 16/17 (94%) achieved clinical remission. Ten patients were male, with a median age of 14.2 years (range 8.6-17.9 years). The majority of the patients had ileocolonic disease (47.4%) or ileocecal disease (42.1%) and an inflammatory behavior (78.9%). None of the patients had growth delay at diagnosis. All patients received EEN orally for six to eight weeks, 18 used polymeric formulas and one used an elemental formula. Comparing data at baseline and after treatment, significant improvements were observed in BMI Z-score (p=0.002), PCDAI score (p<0.001), erythrocyte sedimentation rate (p=0.002), C-reactive protein (p=0.003), faecal calprotectin concentration (p=0.036), and serum albumin (p=0.020). No side effects were noticed. Discussion/Conclusion: In this series, EEN therapy was associated to significant improvement of disease activity index, nutritional status, weight gain and decreased markers of inflammation in most patients. Our data are in accordance with previous observations that EEN is an effective and well tolerated treatment for the induction of remission in pediatric patients with CD.